2021
DOI: 10.1007/s00347-021-01321-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular inflammation with brolucizumab use

Abstract: ZusammenfassungDer VEGF(„vascular endothelial growth factor“)-Inhibitor Brolucizumab ist seit Oktober 2019 in den USA und seit Februar 2020 in Europa zur Behandlung der neovaskulären altersabhängigen Makuladegeneration (nAMD) zugelassen. Grundlage der Zulassung bildeten die randomisierten, doppel-blinden Phase-III-Studien HAWK und HARRIER mit insgesamt 1817 Patienten. Hierbei zeigte Brolucizumab 6 mg (je nach Krankheitsaktivität alle 12 oder alle 8 Wochen verabreicht) eine nichtunterlegene Wirksamkeit in Bezug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
1
16
0
5
Order By: Relevance
“…After the regulatory approval of brolucizumab, a case series of intraocular inflammation with retinal vascular occlusion was reported, some of them with significant vision loss [ 26 , 27 , 28 ]. As a result of these reports, treatment preferences are based on expert opinions, and the impact of treatment choice on visual outcome in real life has remained narrative [ 29 , 30 ]. The pathophysiological basis and risk factors for this IOI signal are currently a topic of intensive research within the community and the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…After the regulatory approval of brolucizumab, a case series of intraocular inflammation with retinal vascular occlusion was reported, some of them with significant vision loss [ 26 , 27 , 28 ]. As a result of these reports, treatment preferences are based on expert opinions, and the impact of treatment choice on visual outcome in real life has remained narrative [ 29 , 30 ]. The pathophysiological basis and risk factors for this IOI signal are currently a topic of intensive research within the community and the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the time of IOI development, four patients developed signs of IOI after the first brolucizumab injection with occurrence of first symptoms after a mean of 19.0±6.5 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) days. Medical attention was sought after a mean of 23.8±6.4 (13-29) days after injection.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…In the meantime, recommendations have been published on the management of patients with nAMD who develop IOI following brolucizumab treatment. 25 Various limitations need to be considered for this study. This is an observational study in a relatively small cohort of 57 patients.…”
Section: Clinical Sciencementioning
confidence: 99%
“…Since recognition of this problem, substantial efforts have been undertaken, primarily driven by Novartis, but also by independent experts to understand this phenomenon 4,[7][8][9] and to provide expert guidelines for its treatment. 2,10,11 Real-world evidence gathered from two large us registries (IRIS and Komodo), together covering 21394 injections, indicates that a history of intraocular inflammation or vascular occlusion in the affected eye results in a tenfold increase in the risk of IOI after Brolucizumab from 0.32-0.41% to 3.97-4.68%. 12 Multiple independent real world case series have meanwhile demonstrated that close monitoring, early diagnosis, aggressive and timely anti-inflammatory treatment as well as discontinuation of Brolucizumab can help to prevent progression to RV/RO and severe vision loss.…”
mentioning
confidence: 99%
“…12 Multiple independent real world case series have meanwhile demonstrated that close monitoring, early diagnosis, aggressive and timely anti-inflammatory treatment as well as discontinuation of Brolucizumab can help to prevent progression to RV/RO and severe vision loss. 2,10,11,13 Once endophthalmitis and other infectious sources of IOI have been excluded, corticosteroid treatment is to be given according to the severity of disease in a standard of care attitude. 9,11 Fundamental for this guidance is the correct interpretation of clinical findings.…”
mentioning
confidence: 99%